Physical Activity Patterns in Adults who are Deaf - Marmeleira, José (2019)
The benefits of physical activity for health are well known, but there is limited information about its patterns in some disability groups. The main purpose of this study was to measure physical activity in a sample of adults who are Deaf. Sixty-two Deaf adults (18-65 years) from both genders (64.3% women) participated. Physical activity was measured by accelerometers worn near the right hip for at least three days. Twenty-nine (~59%) of the 49 participants that met the accelerometer criteria reached the recommendation of 30 min per day of moderate-to-vigorous PA. However, no one achieved that goal in bouts of at least 10 minutes. Participants spent 71% of the accelerometer wear time in sedentary behaviour. It seems that hearing impairment has a lower impact on physical activity habits than other types of disability. Nonetheless, the levels of physical activity could be improved among the Deaf community, especially considering the international recommendations that aerobic activities should be performed in bouts of at least 10 minutes. Future research should collect information on the main barriers and facilitators for physical activity in adults who are Deaf, and strategies should be implemented to promote their engagement in longer bouts of physical activity.